Adaptability and stability of common bean genotypes in family farming systems - Melo, Patricia Guimarães Santos; Alvares, Renata Cristina; Pereira, Helton Santos; Braz, Antônio Joaquim Braga Pereira; Faria, Luis Claudio; Melo, Leonardo Cunha (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the interaction between genotypes and environments for grain yield of common bean (Phaseolus vulgaris) lines and cultivars with potential for use in family farming systems. Data from value for cultivation and use tests, carried out in 20 environments in the state of Goiás, Brazil, were analyzed in two cycles (2007/2008 and 2009/2010) in the dry, rainy, and winter crop seasons. Each test consisted of 15 genotypes from the carioca, purple, and rosinha common bean commercial groups. The experimental design was randomized complete block, with three replicates. The methodologies used to test the stability and adaptability of the genotypes were the one of Lin & Binns, of Cruz, the additive main effects and multiplicative interaction model (AMMI) to calculate the weighted average of absolute scores and productivity (WAASP), and the GGE biplot graphical analysis. The productive performance of the common bean lines and cultivars is affected by genotype x environment interaction. The methodologies adopted allow the selection of cultivars for cropping, and of cultivars and lines for use as parents in order to obtain segregating populations for selection in a family farming system.